Kelebihan dan Kekurangan Jenis-Jenis Media - Nursifa Faujiah; Sekar Nanda Septiani; Tiara Putri (Fakultas Teknik Universitas Muhammadiyah Parepare kerjasama P3M STKIP Muhammadiyah Enrekang, 2022)
In today's digital era, the development of technology and information continues to increase rapidly, thus encouraging the education system to keep up with technological developments so as not to be left behind. Education if conveyed properly and interestingly by utilizing technology as a communication support medium so that quality learning occurs. In an effort to improve the quality of learning and support learning objectives, it is necessary to use various technologies. In order to create success from teaching and learning activities. One of the efforts to improve the quality of learning is by utilizing the use of media or tools to convey the material. There are several types of learning media, namely, audio media, visual media, and audio visual media. However, the use of this media must also be accompanied by an appropriate selection. Because of each type of learning media, of course there are advantages and disadvantages of each. Therefore, in learning, you must be able to choose the right media to convey the material. Given the importance in choosing the right learning media. So in this article, we will describe some of the advantages and disadvantages of each media so that you can find out which ones are appropriate and which are not. Besides that, in order to be able to choose the right media to convey the material, so that the material is conveyed properly and optimally.